(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The research focused on the effects of recycling plastic wrappers and turned into useful materials, such as curtains and picture frames. The study revealed the aspects that may lead to the effects of using plastic wrappers as classroom decoration in grade 12 Accountancy, Business, and Management (ABM) students at Bestlink College of the Philippines. A qualitative method was used in this study by using the descriptive research design. This study involved 50 selected grade 12 ABM students. Three variables, such as students’ discipline and environment cleanliness, were considered as the advantages of recycling plastic wrappers in school materials. Creativity and willingness are factors that students should have to create and make recycled plastic curtains and frames. Students may also be affected if they do not know how to and are unwilling to recycle. The study revealed that recycling has an impact on our lives and our environment. Recycling helps us to save our money and inspire young students to be practical because not all things can be bought others can be recycled.